In Vitro Effect of Zingiber officinale Extract on Growth of Streptococcus mutans and Streptococcus sanguinis. (12th August 2015) - Azizi, Arash; Aghayan, Shabnam; Zaker, Saeed; Shakeri, Mahdieh; Entezari, Navid; Lawaf, Shirin
Abstract : Background and Objectives . Tooth decay is an infectious disease of microbial origin. Considering the increasing prevalence of antibiotic resistance due to their overuse and also their side effects, medicinal plants are now considered for use against bacterial infections. This study aimed to assess the effects of different concentrations of Zingiber officinale extract on proliferation of Streptococcus mutans and Streptococcus sanguinis in vitro. Materials and Methods . In this experimental study, serial dilutions of the extract were prepared in two sets of 10 test tubes for each bacterium (total of 20). Standard amounts of bacterial suspension were added; 100 ƛ of each tube was cultured on prepared solid agar plates and incubated at 37°C for 24 hours. Serial dilutions of the extract were prepared in another 20 tubes and 100 ƛ of each tube was added to blood agar culture medium while being prepared. The mixture was transferred to the plates. The bacteria were inoculated on plates and incubated as described. Results . The minimum inhibitory concentration (MIC) was 0.02 mg/mL for S. mutans and 0.3 mg/mL for S. sanguinis . The minimum bactericidal concentration (MBC) was 0.04 mg for S. mutans and 0.6 mg for S. sanguinis . Conclusion . Zingiber officinale extract has significant antibacterial activity against S. mutans and S. sanguinis cariogenic microorganisms.